Peran Koperasi Syariah Sebagai Pusat Kegiatan Muamalah Jamaah Masjid (Studi Kasus Koperasi Syariah Baitul Mu’min Komplek Pasir Jati, Desa Jati Endah Kecamatan Cilengkrang Kabupaten Bandung) - Intan Nurrachmi; Setiawan Setiawan (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
Besides building and developing the socio-economic potential of members and society, Islamic cooperatives are also the center of muamalah activities in an effort to realize and develop a national economy based on the principles of family and economic democracy. The widespread practice of usury especially in the case of borrowing and investing, and an economy dominated by large companies, makes difficulty for small traders to develop and compete. This resulted in lower economic levels of society. Islamic cooperatives have great potential both in terms of human resources and other supporters. This study examines the role of the Baitul Mu’min Syariah cooperative in reducing the practice of usury and developing the welfare of the Ummah. This is a qualitative research that combines library research and filed research with an empirical approach. The results showed that the Baitul Mu’min Sharia cooperative was established to improve ukhuwah Islamiyah, the spirit of mutual cooperation and help, and to improve the welfare and prosperity of the congregation. It has contributed greatly to the service of the needs of its members and has improved the economy of its members, who are mostly worshipers of the Baitul Mu’min mosque.